Peran Cytidine 5'-diphosphocoline dalam Penatalaksanaan Nyeri Neuropatik - Dessy R Emril (Universitas Syiah Kuala, 2010)
Abstrak. Riview terhadap mekanisme nyeri neuropatik ini adaJah berdasarkan respon yang sangat kompleks terhadap injuri saraf perifer. Terdapat berbagai kemungkinan mekanise yang mendasari terjadinya nyeri neuropatik tennasuk keterlibatan saraf perifer, medulla spinalis, bahkan otak. Penelitian selanjutnya terhadap mekanisme nyeri neuropatik akan membantu kita dalam mengembangkan obat-obat baru yang bekerja pada target tertentu berdasarkan mekanisme yang terjadi. Sehingga prinsip pengobatan yang bersifat simtomatik akan berubah menjadi pengobatan yang bedasarkan mekanisme atau patobiologinya. Dengan dasar pemikiran tersebut saat ini kita sedang mencoba mengembangkan tentang peran Cytidine 5 '-dipbosphocoline dalam penatalaksanaan nyeri neuropatik._(JKS2010; 1:51-62)Kata kunci: nyeri neuropatik, mekanisme nyeri neuropatik, penatalaksanaan, Cytidine 5 '- diphosphocolineAbstract. This brief overview of the known mechanisms of neuropathic pain outlines the complex nature of the responses to a peripheral nerve injury. A unifying hypothesis of a single mechanism of all neuropathic pain is most unlikely to be proven and it is probable that an inter-related portfolio of mechanisms contribute to the generation of neuropathic pain in any given patient, with peripheral, spinal and brain events possibly all playing a role. Further elucidation of mechanisms underlying neuropathy will assist in developing novel targets for drug therapy. It may be possible to improve the ethos of clinical management protocols so that there will be a move away from the current disease based treatment towards symptom or, ultimately, mechanism based therapies. It is a clinical challenge to determine which mechanisms may be operating and hence responsible for individual symptomology in each patient. Mechanism based therapy will require a better understanding of mechanisms involved in neuropathic pain and reliable convenient tools for their assessment in the clinic. According to the established mechanisms, we are trying to elaborate the role ofCytidine 5'-diphosphocoline for the treatment ofneuropathic pain. (JKS 2010; 1:51-62)Keywords: neuropathic pain, NP mechanism, mechanisms based treatment, Cytidine 5'- diphosphocoline